Language in Motion - Time-Typical Vocabulary of Palliative Medicine - Peters, Joachim; Heckel, Maria; Habermann, Mechthild; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2019)
Background Modern palliative medicine is a young discipline that has developed its independent profile with specific guiding concepts, goals and values. The history of the subject and the development of a palliative vocabulary can be explored by analysing specialised publications.
CRIS-Team WoS Importer:2019-05-28